Is the current economic performance compatible with the projected NDP unemployment target? - Mbongeni Zwelakhe Ngubane; Siyabonga Mndebele; Kehinde D. Ilesanmi (Cogent Economics & Finance, 2024)
This study investigated the relationship between unemployment rates and economic growth, known as Okun's Law. The non-linear autoregressive distributed lags (NARDL) model was employed using quarterly time series data sampled from 2000Q1 to 2021Q4. In this model, unemployment was used as the dependent variable, whereas output, exchange rate, and consumer prices index (CPI), were used as explanatory variables, and were decomposed into positive and negative partial sums to capture asymmetry in their effects on unemployment. The findings of this study provided evidence of asymmetry in the effect of all the explanatory variables in the long-run, and a negative relationship is found between output and unemployment. However, unemployment was found more elastic to negative shocks in output than positive shocks. This implies that in the South African labour market, employers are quicker to retrench when the economy is in recession and slower to absorb when the economy is in expansion. Therefore the 6% unemployment target by 2030 appears hypothetical for South Africa, considering its current position. In this regard, this study recommends South African policymakers adjust their labour laws to be more flexible, so that employers do not substitute more labour with capital in the production process. This year 2024 marks twelve years since the National Development Plan (NDP) goals were formulated in South Africa. It is with deep sadness that the society is still characterised by deep poverty, elevated levels of crime and poor living standards. The stimulus packages employed by the South African government and policy uncertainty seem to be not working towards the direction of achieving the projected national development targets. It was necessary to conduct such an investigation to determine if the current economic experience could potentially steer South Africa towards the trajectory of achieving the NDP goals.
Keywords: 330; Unemployment; GDPgrowth; Okun's law; NDP2030 and NARDL; time series; South Africa